2017
DOI: 10.22159/ijpps.2017v9i8.18293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silymarin Extracted From Silybum Marianum on Nickel Hematotoxicity and Nephrotoxicity in Male Albino Wistar Rats

Abstract: Objective: The objective of this study was to investigate the effect of silymarin extract from Silybum marianum against nickel-induced alterations in haematological indices, kidney dysfunction and renal antioxidant defence system. Methods:Male albino Wistar rats were divided into four groups seven each. Control, silymarin, nickel and nickel plus silymarin. Silymarin was administrated orally (100 mg/kg b. wt) and nickel as nickel sulfate (NiSO4 6H2 Results:The treatment with nickel led to a significant decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…In group 5, silymarin administration decreased the elevation in glucose level which was statistically non-significant (P˃ 0.05) compared to the control group. These results were in agreement with who reported that there was an amelioration of blood glucose concentration in nickel animals treated with silymarin extract [50]. It was suggested that the protective role of silymarin was due to its antioxidant properties, an expansion of plasma and pancreatic glutathione concentrations or both [51].…”
Section: Effect On Glucose Liver Kidney and Lipid Function Testssupporting
confidence: 92%
“…In group 5, silymarin administration decreased the elevation in glucose level which was statistically non-significant (P˃ 0.05) compared to the control group. These results were in agreement with who reported that there was an amelioration of blood glucose concentration in nickel animals treated with silymarin extract [50]. It was suggested that the protective role of silymarin was due to its antioxidant properties, an expansion of plasma and pancreatic glutathione concentrations or both [51].…”
Section: Effect On Glucose Liver Kidney and Lipid Function Testssupporting
confidence: 92%
“…Ni is a well-known cytotoxic metal that may affect various organs, particularly liver cells [8]. The metal generates reactive oxygen species (ROS), which lead to lipid peroxidation (LPO), oxidation of DNA, and proteins and results in cell apoptosis [9], immunotoxic [10], hematotoxicity [11], neurotoxic [12], reproductive toxic [13], pulmonary toxic [14], hepatotoxicity [15], and nephrotoxicity [16]. A number of medicinal plants have been described to acquire ROS scavenging and cytoprotective properties [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, traditional medicine is a field that is still in a great demand for research [2]. The traditional medicine aslo safe and no toxic compared to conventional medicine [3,4].…”
Section: Introductionmentioning
confidence: 99%